OCULAR SURFACE COMFORT AND FACE MASKS: DRY EYE EPIDEMIC AMID COVID 19 PANDEMIC? - V. Ivancheva; A. Lyubenov (Trakia Journal of Sciences)
PURPOSE: The purpose of this research is evaluating the effects of wearing face masks on ocular health among medical students in the current COVID-19 pandemic. METHODS: The study includes 147 students in total, all are from Medical University in Pleven. They were interviewed anonymously about their eye health and comfort during periods of wearing face masks. RESULTS: Findings of the study highlighted that wearing face masks for prolonged periods decreases eye comfort levels. Most common presenting complaints were dryness, grittiness, scratchiness, soreness, burning and watering. Almost one quarter of interviewed students sometimes experienced eye fatigue or ocular discomfort. Severity of symptoms was described as “tolerable” in 30.8%, “uncomfortable” in 13%. Of the asked students 25.4% answered that their symptoms were getting worse while being with a protective face mask. In terms of longest uninterrupted time wearing face masks, results show: almost 20% reported more than 5 hours without break. CONCLUSIONS: As a conclusion of this study, it was observed that eye health and dry eye symptoms among medical students was adversely affected by wearing full face covering protective masks during the pandemic situation, which interferes with the quality of life and is an emerging public health issue.